Establishment of a teaching hospital-based dementia consultation service for rurally-based regional district general hospitals - Schott, Björn H.; Voetlause, Jakob Christian; Amoah, Juliana Lisa; Kratzenberg, Alexander; Belz, Michael; Knipper, Tobias; Timäus, Charles; Beskow, Carmen; Sweeney-Reed, Catherine M.; Wiltfang, Jens; Radenbach, Katrin (Frontiers in Public Health, 2022)
Objective The treatment of patients with dementia poses a considerable challenge to regional district general hospitals, particularly in rural areas. Here we report the establishment and initial evaluation of a dementia-specific consultation service provided by a teaching hospital-based Psychiatry Department to regional district general hospitals in surrounding smaller towns. Methods The consultation service was provided to patients with pre-existing or newly suspected dementia, who were in acute hospital care for concurrent conditions. An evaluation of 61 consultations – 49 on-site and 12 via telemedicine – was performed to assess the needs of the participating hospitals and the specific nature of the referrals to the consultation service. Results Suspected dementia or cognitive dysfunction was the primary reason for consultation requests (>50% of cases). Other common requests concerned suspected delirium, behavioral symptoms, and therapeutic recommendations. During the consultations, a diagnosis of dementia was reached in 52.5% of cases, with other common diagnoses including delirium and depression. Recommendations related to pharmacotherapy were given in 54.1% of consultations. Other recommendations included referral for outpatient neurological or psychiatric follow-up, further diagnostic assessment, or assessment in a memory clinic. Geriatric psychiatric inpatient treatment was recommended in only seven cases (11.5 %). Conclusion Our initial evaluation demonstrates the feasibility of providing a dementia-specific consultation service in rural areas. The service has the potential to reduce acute transfers to inpatient geriatric psychiatry and enables older patients with dementia or delirium to be treated locally by helping and empowering rurally-based regional hospitals to manage these problems and associated complications.